Dynamics of energy costs and emissions in operations: analysing energy operational adjustment - Helo, Petri; Mayanti, Bening (Curran associates, 2024)
The amount of energy use in operations and the source of that energy influence the greenhouse gas footprint. This paper analyses the dynamics of energy use in manufacturing where energy price and carbon emission from the grid are hourly fluctuating and vary at different times of the days. Three scenarios are analysed (1) pre-/postponement of operations, (2) storage effect and value, (3) system effect of simultaneous operations. Based on the analyses, we show how different strategies may impact the cost of energy consumed and energy-related emissions. These objectives may be conflicting with each other. A simulator software is presented to analyse the scenarios.
Keywords: decarbonisation; demand respond; energy; operations; sustainability; fi=Tuotantotalous kaupp|en=Industrial Management econ|; fi=Tuotantotalous kaupp|en=Industrial Management econ|